Relation between Weakly Prime Elements and Weakly Prime Sub Modules (Global Journal of Science Frontier Research, 2012)
In this paper we give the defition of weakly prime element of a module. Therefore we give a new definition of factorization in a module, which is called weakly factorization. So we call a module weakly unique factorization which is unique. We give the relation between weakly prime elements and weakly prime sub modules Then we characterize such weakly unique factorization modules.
Keywords: Weakly prime element; weakly prime sub module; factorization